Epidemiology of injuries and illnesses in elite wheelchair basketball players over a whole season - a prospective cohort study - Moritz Weith; Astrid Junge; Tim Rolvien; Sascha Kluge; Karsten Hollander (BMC, 2023)
Abstract Background Wheelchair basketball is an adaptation of pedestrian basketball and one of the most popular Paralympic sports worldwide. The epidemiology of health problems in wheelchair basketball has been prospectively studied only during the Paralympic Games, the 2018 World Championships, the 2021 South America Wheelchair Basketball Championship, and one season of two American intercollegiate wheelchair basketball teams. The objective of the study was to prospectively monitor and analyze the prevalence, incidence, burden, and characteristics of injuries and illnesses in a wheelchair basketball league during an entire season for the first time. Methods All players of the highest German wheelchair basketball league (Bundesliga) were invited to participate in the study. Included players completed the Oslo Sports Trauma Research Center Questionnaire once a week during the entire season 2020/21 to report health problems. Exposure was captured by self-reported training time and officially-recorded competition time. Results Sixty of 117 players (51%, 47 male, 13 female) of the national league participated with an average response of 93%. Seventy health problems (5.5/1000 exposure hours [95% CI: 4.9-6.1]) were reported, including 54 injuries and 16 illnesses. Prevalence of health problems was 60% (95% CI: 48-72). Most injuries affected the shoulder (32% of all injuries), cervical spine/neck (17%), and hand (13%). More overuse injuries (2.9/1000 exposure hours [95% CI: 2.5-3.3]) than acute injuries (1.3/1000 exposure hours [95% CI: 1.0-1.6]) occurred. Of all health problems, 53% were associated with time-loss. The incidences of all health problems, illnesses, injuries, and overuse injuries were higher in women than in men. Conclusions Characteristics and frequency of injuries and illnesses during wheelchair basketball season differed from those during major wheelchair basketball tournaments. The high proportion of overuse injuries and the higher injury rates in women should be regarded in the development of individualized prevention measures. Since results from previous studies during major tournaments are only partially comparable to wheelchair basketball league play, further studies should follow.